Characterization of promising potato clones (solanum tuberosum l. subspecies andigena) for starch extraction (2012)
Colombia has been overproducing potatoes with around 18% remaining unmarketable, constituting a potential alternative use in obtaining native starch for the food industry. To this end, 17 promising potato clones from the Programa de Mejoramiento Genetico of Corpoica were characterized for agronomic variables, as well as physicochemical variables for the tubers. The results were analyzed with descriptive statistics, Pearson correlation and cluster analysis. Clone codified 36 was selected as having potential for the extraction of native starch, showing agronomically: a plant height of 75 cm, a green and undulating stalk, moderate deep purple and white blooming, semi-stellate-shaped corolla, green globe-shaped berries, oval tubers with a creamy white peel color and dotted with purple spots; physicochemically the tubers had: 1.090 specific gravity, 23.12% dry matter, 16.82% starch (22% amylose and 78% amylopectin), 0.122% reducing sugars, 2% protein, 0.82% ash and a pH of 5.69. The extracted starch showed a yield of 53.66% with 19.32% moisture.